Faith as a theme in Mark's narrative - Marshall, Christopher David, 1953- (Cambridge, UK Cambridge UP, 1989)
Includes bibliographical references and indexes.
Based on the author's thesis (doctoral) - University of London, 1985.
Keywords: Faith -- biblical teaching; Bible. N.T. Mark -- criticism, interpretation, etc